Cultural Influence on Sustainability Discourse: A Comparative Analysis of CEO Letters in the Cosmetics and Fashion Industry - Pálffy, Zsuzsanna; Mihályka, Lívia Ablonczy- (Journal of Ecohumanism, 2024)
The national cultural background of a company's founders and managers significantly influences corporate culture and communication. Over the past two decades, the link between culture and sustainability practices has been demonstrated, including how sustainability embeddedness is reflected in CEO letters. This study examines if companies in the cosmetics and fashion industries reveal cultural influences on sustainability in their CEO letters. These letters, the most influential part of annual reports, convey the CEO's vision, operations, and performance. Using quantitative and qualitative content analysis, the research investigates whether national culture influences the content of CEO letters by analysing letters from 15 companies across 10 countries. The study found no statistically significant correlation between Hofstede's cultural dimensions and sustainability narratives in CEO letters. However, feminine cultures tend to have stronger sustainability orientations. These findings suggest that companies should adapt their sustainability communication to align with local cultural values, thereby enhancing stakeholder engagement, particularly for multinational beauty and fashion companies.